IMPORTANCE OF YOGA PRACTICE THROUGH COLORS: रंगो के माध्यम से योग साधना का महत्व - Sharma, Aradhna (International Journal of Research -GRANTHAALAYAH, 2014)
The process of establishing a new look, new emotion, in colors, which is derived from a mixture of inexperienced personalities and experiences, has been used. This is the first aspect of knowledge that is born in human life. That is, the way of working through emotions, which are developed, practiced and experienced. Bhavos are exposed in this way. Which becomes the identity of the pathologist. The humble gesture of adjusting the expressions by marking them in intervals is dynamic. Which is a unique use of the growth momentum to establish the durability of colors. रंगों में नया रूप, नया भाव, स्थापित करने की जो अनुठी लाक्षाणिकता एवं अनुभवों के मिश्रण से प्राप्त इस प्रक्रिया को उपयोग में लाया गया हैं। यह ज्ञार्नाजन का प्रथम पक्ष जो मनुष्य के जीवन में जन्मजात होता हैं। अर्थात भावनाओं के माध्यम से कार्य करने की रीति जिसका विकास, अभ्यास और अनुभव से होता हैं। भावो को इस प्रकार से उधघाटित किया जाता हैं। जो पथ प्रदर्षक की पहचान बन जाती हैं। भावों को अंतराल में अंकित कर समायोजित करने का विनम्र भाव भावात्मक शैली गतिषील होती हैं। जो रंगों का स्थायित्व स्थापित करने की विकास गति का अनूठा प्रयोग हैं।